Publisher Correction: Exogenously overexpressed intronic long noncoding RNAs activate host gene expression by affecting histone modification in Arabidopsis - Zhang-Wei Liu (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.